Proceedings of the 2nd Sari Mulia International Conference on Health and Sciences 2017 (SMICHS 2017) 2017
DOI: 10.2991/smichs-17.2017.60
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness Of Health Promotion Through The Audio Visual Media Risk Of Transmission Of Hiv / Aids On The Motivation Of Youth In Sman 10 Banjarmasin

Abstract: Objective: To analyze the influence of Health Promotion through Audio Visual Media about the risk of HIV/AIDS transmission to Motivate Of Adolescents in SMAN 10 Banjarmasin Method: One group pretest-posttest research was conducted on May 20, 2017, at SMAN 10 Banjarmasin. This research was conducted on 66 students of class XI with cluster sampling technique was taken representatives of 11 people from each class XI IPA IPS. Data were collected using questionnaire, then analyzed using Wilcoxon test. Result:The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 1 publication
0
4
0
1
Order By: Relevance
“…These values are congruent with the outcome of a previous study by Arneliwati, Agrina and Dewi, which showed a larger number of female than male visitors. 6 Meanwhile, the Public Health Center provides services for women experiencing health challenges, and also for the routinary pregnancy and postpartum checks, and contraceptive services. Some differences were observed between both sexes in the level of attention payed to an object, and women had a higher tendency to pay attention to symbolic items.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These values are congruent with the outcome of a previous study by Arneliwati, Agrina and Dewi, which showed a larger number of female than male visitors. 6 Meanwhile, the Public Health Center provides services for women experiencing health challenges, and also for the routinary pregnancy and postpartum checks, and contraceptive services. Some differences were observed between both sexes in the level of attention payed to an object, and women had a higher tendency to pay attention to symbolic items.…”
Section: Discussionmentioning
confidence: 99%
“…This result was consistent with a research by Arneliwati, Agrina and Dewi. 6 Other investigations linked a higher level of education with better attentiveness, especially at advanced levels, as seen with divided and sustained attention. However, the inverse is observed with students at low-class, which also indicates the influence of age, hence it is believed that education trains an individual to increase attention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hasil tersebut juga didukung oleh penelitian yang dilakukan oleh Ahmad Syahlani (2017), dalam penelitianya menunjukan bahwa penggunaan media audio visual sebelum promosi kesehatan 56 orang (84,8%) negatif dan setelah promosi kesehatan 60 orang (90,9%) positif dengan p-value 0,000. Sebelum promosi 53 orang (80,3%) memiliki motivasi rendah dan setelah promosi kesehatan, ada 55 orang (83,3%) memiliki motivasi tinggi dengan p-value 0,000, hal ini dapat disimpulkan bahwa ada pengaruh promosi kesehatan melalui media audio visual tentang risiko penularan Hiv/Aids terhadap motivasi remaja 27 .…”
Section: Analisis Pengaruh Edukasi Dengan Media Video Terhadap Tingka...unclassified